PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to examine the effect of work motivation and leadership style on employee job satisfaction through Organizational Citizenship Behavior on employees at PT. Sari clumps Medini Kendal. Population of 149 people, with purposive sampling technique sampling obtained a sample of 102 employees. Techniques of data analysis: test validity by factor analysis, reliability testing with Alpha Chrombach, model test with Adjusted R2 and F-test, hypothesis testing with multiple linear regression and t test. The results: motivation and leadership style has a positive effect on jobnsatisfaction of employees, either directly or through mediation Organizational Citizenship Behavior.Keywords: Motivation, Leadership Style, Organizational Citizenship Behavior, Job Satisfaction.